OPTIMAL CONTROL OVER THE DISTRIBUTE ELECTRIC ENERGY SOURCES WITH ASYNCHRONOUS GENERATORS BY SMART GRID - Kulyk, Volodymyr; Magas, Taras; Malogulko, Yulia (Scientific Works of Vinnytsia National Technical University, 2015)
The paper, in accordance with the conception of Smart Grid, considers some questions of formation of intellectual electric nets, the solution of which will allow to create the prerequisites for efficient use of dispersed sources of electric energy.